Cumulative Amount of Intravenous Lipid Intake and Parenteral Nutrition-Associated Cholestasis in Neonates with Gastrointestinal Surgical Disorders - Nayrouz, Mazen M.; Amin, Sanjiv B. (American Journal of Perinatology, 2014)
Objective To evaluate if cumulative amount of intravenous lipid (IL) intake is associated with severity of parenteral nutrition (PN)-associated cholestasis (PNAC) in neonates with gastrointestinal surgical disorders (GISD).Study Design The authors performed a retrospective study including 36 neonates > 34 weeks gestational age with GISD. Neonates with metabolic liver disorders, chromosomal disorders, TORCH infections, which includes toxoplasmosis, other (syphilis, varicella-zoster, parvovirus B19), rubella, cytomegalovirus (CMV), and herpes, biliary tract anomalies, or direct hyperbilirubinemia (DHB) within first postnatal week were excluded.Results There was no significant difference in clinical factors between three groups of neonates: (1) without PNAC (n = 13), (2) with mild-to-moderate PNAC (DHB 1–5 mg/dL, n = 12), and (3) with severe PNAC (DHB > 5 mg/dL or PNAC with elevated amino-transaminases, n = 11) except for duration of enteral starvation and PN. Using ordered logistic regression, cumulative amount of IL, glucose, and protein intake were independently associated with severity of PNAC (p < 0.05). Comparing macronutrients as predictors of severe PNAC using receiver operating characteristic curves, the area under the curve for IL (0.583) intake was significantly larger (p = 0.008) compared with intravenous protein (0.257) and glucose (0.431) intake.Conclusions IL intake is associated with and is a better predictor of severity of PNAC in neonates with GISD.
Keywords: late preterm neonates; hepatic dysfunction; direct hyperbilirubinemia; lipid